Technical Pitfall in 68Ga–Prostate Specific Membrane Antigen Imaging: Altered Biodistribution Caused by Free 68Ga-Citrate Due to Radiolysis Showing Increased Vascular Activity. (June 2018) - Hod, Nir; Anconina, Reut; Levin, Daniel; Ezroh Kazap, Dina; Lantsberg, Sophie
Abstract : Abstract: As with any new molecular imaging modality, accurate characterization of abnormalities on 68 Ga-PSMA PET/CT imaging can be accomplished only if one is aware of the normal distribution pattern, physiological variants, and potential sources of false imaging findings. Altered biodistribution can have a significant impact on scan interpretation. Presented here is a rare case in which radiopharmaceutical radiolysis occurred causing excessive free 68 Ga-citrate showing as an increased vascular activity. As 68 Ga-PSMA PET/CT imaging is a relatively new imaging technique, it is important to be aware of such a potential technical pitfall in clinical practice in order to prevent scan misinterpretation.